Design and Analysis of a Low Cost Wave Generator Based on Direct Digital Synthesis. (17th September 2015) - Qi, Jian; Sun, Qun; Wu, Xiaoliang; Wang, Chong; Chen, Linlin
Abstract : Signal generators are widely used in experimental courses of universities. However, most of the commercial tests signal generators are expensive and bulky. In addition, a majority of them are in a fixed working mode with many little-used signals. In order to improve this situation, a small sized and highly accurate economic signal generator based on DDS technology has been developed, which is capable of providing wave signals commonly used in experiments. Firstly, it is introduced the basic principles of DDS and is determined the overall scheme of the signal generator. Then, it proposes a design of the hardware, which include power supply module, display module, keyboard module, waveform generating module based on DDS chip, and the minimum system module based on C8051F010. The signal generator was designed to output sine and square waveforms, and the other achieved performances included the frequency range 0.1 Hz–12.5 MHz, the frequency resolution 0.05 Hz–0.1 Hz, the output amplitude 1.0–4.5 V, the frequency accuracyK f min = 94.12 % andK f max = 99.99 %, and the signal distortionR THDmin = 0.638 % andR THDmax = 11.67 %.